2016
DOI: 10.4103/2229-3485.192039
|View full text |Cite
|
Sign up to set email alerts
|

A study of medication errors in a tertiary care hospital

Abstract: Objective:To determine the nature and types of medication errors (MEs), to evaluate occurrence of drug-drug interactions (DDIs), and assess rationality of prescription orders in a tertiary care teaching hospital.Materials and Methods:A prospective, observational study was conducted in General Medicine and Pediatric ward of Civil Hospital, Ahmedabad during October 2012 to January 2014. MEs were categorized as prescription error, dispensing error, and administration error (AE). The case records and treatment cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
20
1
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(40 citation statements)
references
References 15 publications
3
20
1
2
Order By: Relevance
“…Drug interaction results in toxic effects or therapeutic failure. DDIs cover 6–30% of all adverse drug events [12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Drug interaction results in toxic effects or therapeutic failure. DDIs cover 6–30% of all adverse drug events [12].…”
Section: Introductionmentioning
confidence: 99%
“…Excessive and inappropriate prescribing results in severe consequences such as wastage of the public economy, increased risk of toxicity, increased adverse drug reaction, increased antimicrobial resistance and decreased faith in the medical profession [18]. Poor communication between patients and prescribers, self-medication and unethical medicine promotion has been reported to increase irrational prescribing [12]. The pharmacists play a vital role in the detection and prevention of potential prescription errors.…”
Section: Introductionmentioning
confidence: 99%
“…A study by Patel et al has reported medication administration error is common in pediatric patients. [ 18 ] This calls for need of training of health-care workers and monitoring following vaccination.…”
Section: Discussionmentioning
confidence: 99%
“…Así, este artículo expuso que los errores de dispensación que observaron en el estudio fueron medicamentos prescritos no dispensados y, por lo tanto, tuvieron consecuencias de la omisión. De las 15 omisiones que advirtieron, hubo una muerte por falta de dosis de atropina en la intoxicación por organofosforados [26] 3.1.4.4. Errores de medicación relacionados con el proceso de administración.…”
Section: Distribución De Los Errores De Medicación Durante Las Etapasunclassified